EFL Pre-service Teachers' Satisfaction of Online English Learning and Their Academic Achievements - Murtiningsih, Sri Rejeki; Islamiyati, Alyda Rizka; Hidayatulloh, Sibakhul Milad Malik (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2023)
The transformation of face-to-face classrooms into online classes during the Pandemic Covid 19 has impacted ELT activities. One of which is the students' satisfaction with the new format of learning. The aim of this study was to investigate the relationship between English Foreign Learning (EFL) Pre-service Teachers’ satisfaction with online English learning and their academic performance. A quantitative study with a correlational design was adopted to investigate the issue. A convenience sample strategy was used to recruit 132 EFL pre-service teachers from a private university in Yogyakarta. An online survey was administered to garner the data as well as students’ GPAs were used as another criteria. The Kendall's Tau correlation value (-value) of this study was 0.023, with a significance value of 0.704 (0.704>0.05). It suggests that the alternative hypothesis has been ruled out. Consequently, the research revealed that there was a statistically insignificant correlation between the level of satisfaction of EFL Pre-service Teachers' experience with online English learning and their academic performance. Even so, teachers and institutions are expected to still maintain the quality of online learning for their students.